A New Horizon of Liquid Biopsy in Thymic Epithelial Tumors: The Potential Utility of Circulating Cell-Free DNA - Ottaviano, Margaret; Giuliano, Mario; Tortora, Marianna; La Civita, Evelina; Liotti, Antonietta; Longo, Michele; Bruzzese, Dario; Cennamo, Michele; Riccio, Vittorio; De Placido, Pietro; Picozzi, Fernanda; Parola, Sara; et al. (Frontiers in Oncology, 2021)
Background: Thymic epithelial tumors (TETs) are rare thoracic malignancies, commonly divided into two different histopathological entities, thymoma (T) and thymic carcinoma (TC). To date, there are no specific biomarkers for monitoring the biological course of these rare tumors. We carried out a single center study aiming at the detection of circulating cell-free DNA (ccfDNA) and the correlation of its levels with metastatic dissemination and histological subtype in patients with TETs. Methods: From July 2018 to January 2020, 5 mL blood samples from 26 patients with advanced TET (aTET) (11 patients with TC and 15 patients with T) and from 6 patients with completely resected TET (cr-TET), were prospectively obtained before the initiation of systemic therapy. Blood samples from 10 healthy donors were used as control. The QIAamp MinElute ccfDNA Kits was used for ccfDNA isolation from plasma; real-time PCR was used for cfDNA quantification. Results: We found significantly higher ccfDNA amount in patients with T and TC compared to controls, with median ccfDNA level of 3.3 ng/µl, 11.4 ng/µl and 25.6 ng/µl, for healthy donors, T and TC patients, respectively (p<0.001). No significant difference was found between cr-TET and controls (p= 0.175). ccfDNA concentrations were higher in metastatic (M1a and M1b) compared to non-metastatic (M0) TETs (25.6 ng/ul versus 7.2 ng/ul; p= 0.037). No significant correlation was found either between ccfDNA and disease stage, according to both the Masaoka-Koga (p= 0.854) and the TNM8th edition staging systems (p=0.66), or between ccfDNA levels and overall tumor burden, estimated according RECIST 1.1 criteria (r= 0.07, p= 0.725). Conclusions: To the best of our knowledge, this is the first study that prospectively explores detection and quantification of ccfDNA in TETs. Higher baseline cfDNA levels have been observed in both advanced T and TC comparing to the control group.